Belajar Bahasa Mandarin melalui Lagu - Dyah Tjaturrini; Kumala Dewi Wundari; Maherta Enggar Pramudya (Universitas Pahlawan Tuanku Tambusai, 2022)
Song has a universal appeal that connects all cultures and languages. Besides the potential to make learning interesting and fun, songs as authentic materials are very versatile and can be developed into various learning activities. The purpose of this service activity is to improve speaking and listening skills in Mandarin and master vocabulary more easily. The methods we use in this activity are demonstrations and training. The results of this service activity can be concluded 2 things; Mandarin song applications can improve four competencies in learning foreign languages and can increase children's motivation in learning foreign languages. In addition, it is hoped that the use of songs as a learning medium can provide new references as a way to increase children's learning motivation used in teaching and learning activities (KBM).